Investments in the human capital of the socially disadvantaged children: Effects on redistribution - Tim Lohse; Peter F. Lutz; Christian Thomann (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
Recently, early investments in the human capital of children from socially disadvantaged environments have attracted a great deal of attention. Programs of such early intervention, aiming at children's health and well-being, are spreading considerably in the U.S. and are currently tested in several European countries. In a discrete version of the Mirrlees model with a parents' and a children's generation we show the intra-generational and the inter-generational redistributional consequences of such intervention programs. It turns out that the parents' generation always loses when such intervention programs are implemented. Among the children's generation it is the rich who always benefit. Despite the expectation that early intervention puts the poor descendants in a better position, our analysis reveals that the poor among the children's generation may even be worse off if the effect of early intervention on their productivity is not large enough.
Keywords: I38; J13; H21; I14; 330; Early Intervention; welfare; redistribution; taxation